U.S. monetary and fiscal policy regime changes and their interactions - Yoosoon Chang; Boreum Kwak; Shi Qiu (Halle Institute for Economic Research (IWH), 2021)
We investigate U.S. monetary and fiscal policy interactions in a regime-switching model of monetary and fiscal policy rules where policy mixes are determined by a latent bivariate autoregressive process consisting of monetary and fiscal policy regime factors, each determining a respective policy regime. Both policy regime factors receive feedback from past policy disturbances, and interact contemporaneously and dynamically to determine policy regimes. We find strong feedback and dynamic interaction between monetary and fiscal authorities. The most salient features of these interactions are that past monetary policy disturbance strongly influences both monetary and fiscal policy regimes, and that monetary authority responds to past fiscal policy regime. We also find substantial evidence that the U.S. monetary and fiscal authorities have been interacting: central bank responds less aggressively to inflation when fiscal authority puts less attention on debt stabilisation, and vice versa.
Keywords: C13; C32; E52; E63; 330; monetary and fiscal policy rules; endogenous regime switching; joint estimation; policy interactions; feedback channels